Lecturers’ Perspective on the Use of Artificial Intelligence (AI) in Students’ English Writing Products: A Narrative Inquiry Study - Masrur, Irfan (Universitas Al-Qolam Malang, 2022)
This study investigates lecturers’ perspectives on the use of AI in students’ English writing products within English Language Departments around Jember. Employing a narrative inquiry approach, the research captures the personal experiences, reflections, and interpretations of six English lecturers who have directly encountered AI-assisted student writing. The findings indicate that lecturers generally view AI as a supportive learning tool that can help students improve grammar accuracy, vocabulary choice, and text coherence. However, they simultaneously express concern regarding issues of authenticity and academic integrity, noting that excessive dependence on AI may limit students’ critical thinking and genuine writing development. Lecturers also highlight the urgent need for institutional policies and AI literacy, emphasizing that students must be guided to use AI responsibly and transparently. Overall, the study reveals a balanced yet cautious stance among lecturers, acknowledging both the pedagogical benefits and ethical challenges of AI-assisted writing. These insights contribute to broader discussions on integrating AI into higher education and developing frameworks for its ethical use in English writing instruction.